Dari Fatwa ke Kebijakan Luar Negeri: Analisis Maqāṣid al-Sharī‘ah terhadap Fatwa MUI Tahun 2024 tentang Hubungan Internasional - Bianda, Ryan; Gunaepi, Aang; Yosef Niteh, Muhammad; Ahmad, Maad (Institut Agama Islam Negeri Kendari, 2026)
The growing complexity of global diplomacy and ethical governance urges scholars to revisit Islamic legal reasoning as a moral compass in international relations. This study aims to analyze the 2024 Fatwa of the Indonesian Council of Ulama (MUI) on the Principles of International Relations through the framework of maqāṣid al-Sharī‘ah. Using a qualitative normative approach, the research examines theological foundations, juridical arguments, and ethical implications by comparing the fatwa’s substance with classical Islamic legal sources and contemporary global ethics. The findings indicate that the fatwa operationalizes maqāṣidic principles such as justice, the preservation of life, and human dignity, affirming Islam’s compatibility with universal humanitarian norms. It further positions Islamic jurisprudence as a constructive partner in global governance through moral diplomacy grounded in compassion and fairness. The integration of maqāṣid al-Sharī‘ah within diplomatic frameworks highlights its potential to guide ethical policymaking and promote global solidarity. Ultimately, the fatwa redefines the role of Islamic law in shaping inclusive and humane diplomacy, offering a normative model for ethical engagement in international affairs.